W18O49@EP nanoparticles improve the anti-tumor effect of radiotherapy and photodynamic therapy by avoiding the limitation of hypoxia - Wang, Jianquan; Hao, Lingyun; Li, Xinhua; Liu, Sen (Frontiers in Bioengineering and Biotechnology, 2022)
Insufficient oxygen supply at the tumor site and hypoxia caused during tumor treatment lead to a poor therapeutic effect and poor prognosis. Therefore, effectively overcoming the problem of hypoxia in tumors and avoiding hypoxia that compromises the efficacy of the treatment could improve the anti-tumor therapeutic effect. Thus, this study reports the ability of W18O49@EP nanoparticles to release reactive oxygen species (ROS) during the combined tumor radiotherapy (RT) and photodynamic therapy (PDT). The release of ROS by the nanoparticles during near infrared light (NIR) irradiation was demonstrated by in vitro and in vivo experiments, realizing an effective PDT without inducing hypoxia. Indeed, the ROS did not derive from the oxygen in the tumor microenvironment but they were released by the nanoparticles. Thus, ROS could improve the therapeutic effect of RT avoiding the problem of hypoxia after RT. Hence, W18O49@EP nanoparticles greatly improved the anti-tumor effect due to their effectiveness despite the insufficient oxygen supply and hypoxia caused by traditional RT and PDT.